Dual Effects of a RETN Single Nucleotide Polymorphism (SNP) at –420 on Plasma Resistin: Genotype and DNA Methylation - Onuma, Hiroshi; Tabara, Yasuharu; Kawamura, Ryoichi; Ohashi, Jun; Nishida, Wataru; Takata, Yasunori; Ochi, Masaaki; Nishimiya, Tatsuya; Ohyagi, Yasumasa; Kawamoto, Ryuichi; Kohara, Katsuhiko; Miki, Tetsuro; et al. (The journal of clinical endocrinology and metabolism, 2017)
Methylation at RETN SNP–420 was inversely associated with plasma resistin dependent and independent of SNP–420 genotypes in the general Japanese population.AbstractContext:We previously reported that single nucleotide polymorphism (SNP)–420 C>G (rs1862513) in the promoter region of RETN was associated with type 2 diabetes. Plasma resistin was tightly correlated with SNP–420 genotypes. SNP–420 is a CpG-SNP affecting the sequence of cytosine–phosphate–guanine dinucleotides.Objective:To examine whether methylation at SNP–420 affects plasma resistin, we analyzed plasma resistin and methylation at RETN SNP–420.Design and Methods:Genomic DNA was extracted from peripheral white blood cells in 2078 Japanese subjects. Quantification of the methylation was performed by pyrosequencing after DNA bisulfite conversion.Results:Methylation at SNP–420 was highest in the C/C genotype (36.9 ± 5.7%), followed by C/G (21.4 ± 3.5%) and G/G (2.9 ± 1.4%; P < 0.001). When assessed in each genotype, methylation at SNP–420 was inversely associated with plasma resistin in the C/C (β = –0.134, P < 0.001) or C/G (β = –0.227, P < 0.001) genotype. In THP-1 human monocytes intrinsically having the C/C genotype, a demethylating reagent, 5-aza-dC, decreased the methylation at SNP–420 and increased RETN messenger RNA. SNP+1263 (rs3745369), located in the 3′ untranslated region of RETN, was also associated with methylation at SNP–420. In addition, highly sensitive C-reactive protein was inversely associated with methylation at SNP–420 in the C/C genotype, whereas body mass index was positively associated.Conclusions:Plasma resistin was inversely associated with the extent of methylation at SNP–420 mainly dependent on the SNP–420 genotype. The association can also be explained partially independent of SNP–420 genotypes. SNP–420 could have dual, genetic and epigenetic effects on plasma resistin.